Assimilation, Psychological Distress, and Family Functioning among Iranian Immigrant Families in Manchester, England - Alemi, Mandana (2010)
Emigration from one country to another with different cultural conditions involves a great risk for an immigration crisis that can lead to great strain and stress, which in turn affects family life negatively.Immigration places immigrant families in a new situation in which values, norms, experiences, and roles are questioned and in which family members come into conflict with one another. In order to survive in the new situation, families may strive toward a harmonious existence within the host society.As social system and values differ across countries, the process of assimilation is always needed. Based on the problems mentioned, this study attempted to elicit the process of assimilation, to investigate the psychological distress, and to explore the patterns of family functioning among Iranian immigrant families in Manchester,Britain.